Investigating Multiliteracy Pedagogy Practices of EFL-Speaking Teachers in Indonesia - Desi Surlitasari Dewi; Rudi Hartono; Mursid Saleh; Sri Wahyuni (Universitas Negeri Semarang, 2023)
This study aims to investigate the multiliteracy pedagogy practices used by EFL-speaking teachers in Indonesia. The study consists of two research questions: 1) How do EFL-speaking teachers in Indonesia implement Multiliteracy Pedagogy in their teaching practices? 2) What are the perceived benefits of using multiliteracy pedagogy practices in EFL-speaking classrooms in Indonesia? The data were collected through open questionnaire and in-depth interview. Open questionnaires were distributed to 19 EFL-speaking teachers in Indonesia. The results indicate that these teachers are implementing some elements of multiliteracy pedagogy, and they use various modes, such as visual, audio, audiovisual, or gestural, to support their teaching. Then, interview was conducted to small sample of the respondents. The data were analyzed through content and thematic analysis. The findings show that multiliteracy pedagogy practices make learners become more active thinkers, more independent learners, and are more engaged in their learning. The benefits of using multiliteracy pedagogy practices in EFL-speaking classrooms in Indonesia include improving learners’ language proficiency, promoting critical thinking and problem-solving skills, and enhancing learners’ motivation and engagement. Overall, this study contributes to a better understanding of the current multiliteracy pedagogy practices used by EFL-speaking teachers in Indonesia and sheds light on how these practices are integrated into teaching. The findings suggest that multiliteracy pedagogy practices have several benefits for EFL-speaking learners in Indonesia.